Proceedings of the 34th International Power Sources Symposium
DOI: 10.1109/ipss.1990.145823
|View full text |Cite
|
Sign up to set email alerts
|

Performance of lithium-sulfur dioxide rechargeable cells

Abstract: The lithium-sulfur dioxide rechargeable system has been investigated with LiAlC14 electrolyte in hermetically sealed experimental cells. Over 50 cells were tested at 1-6 mA/cm2 discharge and 0.5-2 mA/cm2 charge rates using carbon cathode material to evaluate cycle life and capacity at ambient (21OC) and low (-30°C) temperatures. Most of the cells delivered excellent cycle life with significantly higher capacity than that reported in the literature.Optimization of the cathode process, cell configuration and ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The sulfoxy reduction product of the Li/LiA1C14 9 xSO2/C cells is known not to be crystalline. 6 If the product does contain $20~-groups then these could either be in the eclipsed or staggered forms. If the $20~-ion were coordinated to AP § via S, then it would be expected to be i n the eclipsed form, with both S atoms interacting with A1.…”
Section: Resultsmentioning
confidence: 99%
“…The sulfoxy reduction product of the Li/LiA1C14 9 xSO2/C cells is known not to be crystalline. 6 If the product does contain $20~-groups then these could either be in the eclipsed or staggered forms. If the $20~-ion were coordinated to AP § via S, then it would be expected to be i n the eclipsed form, with both S atoms interacting with A1.…”
Section: Resultsmentioning
confidence: 99%
“…The merits of these batteries are based on some promising physical and electrochemical properties of the SO 2 -based inorganic electrolyte including (i) nonflammability, (ii) high ionic conductivity (∼10 –1 S cm –1 ), and (iii) versatile use as an electroactive catholyte or solely as an ion-conducting electrolyte. For a Li–SO 2 battery, remarkable improvement of battery performance could be also achieved by exploiting various carbon nanostructured materials for the cathode materials . However, a Li metal anode in the Li–SO 2 systems still suffers from the dendritic growth of Li metal during cycling. Not only was scattered needle-like Li deposited but cracks on the surface of Li metal were also observed . Therefore, these problems should be resolved for successful application of Li–SO 2 batteries.…”
Section: Introductionmentioning
confidence: 95%
“…20−22 Not only was scattered needle-like Li deposited but cracks on the surface of Li metal were also observed. 23 Therefore, these problems should be resolved for successful application of Li−SO 2 batteries. We previously reported that a highly concentrated Na +conducting inorganic electrolyte provided a compact and dense SEI layer for the Na metal anode, leading to the suppression of dendritic growth of Na and improved electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%
“…Primary Li–SO 2 batteries in which liquefied SO 2 serves as the active cathode material have been commercialized for military and industrial applications910, and ongoing interest for further development is still found11. About 30 years ago, there were also intensive studies on Li–SO 2 rechargeable batteries based on a LiAlCl 4 ⋅ x SO 2 inorganic molten complex catholyte, which shows completely different reaction chemistry from the primary SO 2 battery81213141516. Rechargeable Li–SO 2 battery showed a discharge capacity of ~1000 mAh g −1 based on the carbon electrode (theoretical catholyte capacity of 144 mAh g −1 for LiAlCl 4 ⋅6SO 2 ) with an operating voltage of 3.2 V, and Duracell demonstrated the performance of prototype C-size Li–SO 2 rechargeable batteries12.…”
mentioning
confidence: 99%